Exploring physical and chemical properties in new multifunctional indium-, bismuth-, and zinc-based 1D and 2D coordination polymers - Gomez, Germán Ernesto (2018)
Main group element coordination polymers (MGE-CPs) are important compounds for the development of multifunctional materials. However, there has been a shortage of studies regarding their structural, optical, catalytic, mechanical, and antibacterial properties. This work presents an exhaustive study of a set of crystalline MGE-CPs obtained from bismuth and indium metals and iminodiacetate, 1,2,4,5-benzenetetracarboxylate, and 2,2′-bipyridine as building blocks. An in-depth topological analysis of the networks was carried out. Additionally, nanoindentation studies were performed on two representative low-dimensional compounds in order to find the relationships between their structural features and their intrinsic mechanical properties (hardness and elasticity). The solid-state photoluminescence (SSPL) properties were also studied in terms of excitation, emission, lifetimes values, and CIE chromaticites. Moreover, the heterogeneous catalytic activities of the compounds were evaluated with the cyanosilylation reaction using a set of carbonylic substrates under solvent-free conditions. Finally, the inhibitory effect of the Bi-CPs on the growth of microorganisms such as Escherichia coli, Salmonella enterica serovar Typhimurium, and Pseudomonas aeruginosa, which are associated with relevant infectious diseases, is reported.